Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Bagi UMKM Kelurahan Kelayu Selatan Kecamatan Selong Kabupaten Lombok Timur - Salmi Yuniar Bahri; Yuniar Affandy; Masbullah Masbullah; Nova Hari Shanty (Lembaga Pengembangan Kinerja Dosen, 2025)
Business legality is a very important component in the development of micro, small, and medium enterprises (MSMEs). Business legality provides MSME players with legal protection, easier access to financing, and greater opportunities for growth. The Business Identification Number (NIB) is the official identity of business actors used to obtain business licenses and commercial or operational permits through an integrated electronic licensing system, namely Online Single Submission (OSS). The objective of this community service program is to increase the understanding and awareness of MSME actors in Kelayu Selatan Village, Selong District, East Lombok Regency, regarding business legality, particularly the creation of an NIB. To support more efficient assistance tailored to the needs of each business operator, this activity was conducted door-to-door and included several stages, such as observation and data collection on MSMEs, dissemination of information on the importance of business legality, assistance in creating OSS accounts, and assistance in the application process until the issuance of the NIB. The results of the activity showed an increase in awareness and knowledge about the importance of business legality. It is hoped that this program will encourage MSMEs to transform into formal businesses that are competitive and sustainable.